The Eye of the Chiropterologist: Phenotypic Versus Genotypic Identification of Bats - F. D. Dami; T. E. Adeyanju; A. A. Chaskda; I. M. Okpanachi; A. T. Adeyanju; S. M. Ezekiel; T. Gwom; I. A. Iniunam; A. Hitch; D. D. Pam; P. Luka; S. C. Weaver; et al. (Ecology and Evolution, 2025)
ABSTRACT Bats are a diverse and ecologically important group of mammals that play critical roles in ecosystems. Accurate identification is necessary to comprehend bat species' ecology and behavior to further the conservation of bats. Both phenotypic and genotypic methods have been used for bat identification, but their relative effectiveness remains unclear in the Afrotropics. This study compared the advantages and limitations of phenotypic and genotypic identification of bats to improve and ensure effective bat species identification. Bats were captured using mist nets within protected and unprotected areas in different vegetation zones in Nigeria. Morphological identification of all captured bats was done using the guide, Mammals of Africa. Genotypic identification was done by extracting genomic DNA and Sanger sequencing of the generated mtDNA PCR amplicons. We then compared the sensitivity, specificity, positive predictive value (PPV) and negative predictive value (NPV) of the phenotypic to the genotypic outcomes of our identification. We trapped 91 bats, and the phenotypic identification of 90 individual species showed sensitivity ranges between 68% and 100%, except for Glauconycteris spp., whose sensitivity was low (14%). The specificity was generally good for all species > 96%. Phenotypic identification is accurate and reliable for most trapped bat species (Epomorphorus gambianus, Scotophilus spp., Micropteropus pusillus, Rhinolophus spp., Roussettus aegyptiacus, and Chaerephon spp.). However, phenotypic identification reveals its limitations in some bat species such as Banana pipistrellus and Glauconycteris spp., which had more variable results from their genetic characterization. Epomorphorus gambianus and Micropteropus pusillus had no distinct genetic differentiation in their mtDNA. This highlights the importance of using multiple methods for bat identification to ensure the most accurate results.